PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MENGGUNAKAN MODEL PEMBELAJARAN PICTURE AND PICTURE DI KELAS IV SD ANGKASA LANUD SUTAN SJAHRIR PADANG - Afina, Indah; Suriani, Ari; Rahmi, Gita; Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was conducted in response to the low narrative writing skills of fourth-grade students at Angkasa Lanud Sutan Sjahrir Elementary School, in Padang. This condition was attributed to the learning model, which had not yet effectively optimized students’ engagement in the learning process, resulting in difficulities in generating ideas for narrative writing. The study aimed to describe the improvement of students’ narrative writing skills through the implementation of the Picture and Picture learning model. The study employed Classroom Action Research (CAR) using both quantitative and qualitative approaches. It was conducted in two cycles, with each cycle consisting of four stages: planning, implementation, observation and reflection. Data were collected through observation, test, and non-test techniques. The participants included the classroom teacher as the observer, the researcher as the practitioner, and 22 fourth-grade students of Angkasa Lanud Sutan Sjahrir Elementary School, in Padang. The findings indicated that the quality of the teaching module improved from 89.5% in cycle-I to 95.8 in cycle-II. Teacher activity also increased from 87.45% to 97.2%, while students’ learning activity improved from 88.85% to 97.2%. In addition, the average score of students’ narrative writing skills increased from 80.25 in cycle-I to 85 in cycle-II. These findings indicate that the implementation of the Picture and Picture learning model effectively improved the narrative writing skills of fourth-grade students at Angkasa Lanud Sutan Sjahrir Elementary School, in Padang.